2017Spring PaduaMuscleDays, roots and byproducts - Ugo Carraro (PAGEPress Publications, 2017)
The second 2017 issue of EJTM volume 27 contains the collection of abstracts from the 2017Spring PaduaMuscleDays conference, that was held March 23-25 in Montegrotto, Euganei Hills, Padova, Italy. In addition to a brief history of the Padova Myology Meetings held during the last 30 years, the present and the future of the PaduaMuscleDays conference are discussed with special reference to new media and the options they offer to spread to a larger audience the results of the many workshops held in the Hotel Augustus conference hall and in the Aula Guariento of the Accademia Galileiana di Scienze, Lettere ed Arti, one of the hidden treasures of the medioeval Padua, Italy. Preliminary announcements of the 2017 and 2018 events, in particular of the Giovanni Salviati Memorial, will follow.